Computational Analysis of the Structural Composition of Coronavirus Genomes - M. V. Sprindzuk; V. I. Bernik; A. S. Vladyko; L. Zhuozhuang; L. P. Titov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2023)
Ecological disasters, wars in regions with microbiological weapons depots, deforestation, domestication of wild animals, consumption of infected animals, contamination of water and food products and their components, experiments with viruses, deficiencies and other defects of the immune system in modern humans and other mammals became the impetus for the evolution of new dangerous and extremely dangerous viruses. Due to the emergence of new dangerous viruses, the importance and demand for knowledge and skills of computational biology, epidemiology and virology in modern society have increased. Modern sequencers are capable of producing large amounts of bioinformatic data that is represented in the form of genomic texts. Comparative сomputational analysis of this information is necessary to clarify the issues of phylogenesis, mutational profiling, molecular evolution, identification of insertions of other genomes, annotation of genome regions, search for targets for vaccine development and pharmacotherapy. In this сontext, authors conducted a computational experiment of comparative analysis of the genomic texts of Belarusian coronavirus samples against a number of selected complete genomes of dangerous and extremely dangerous viruses and coronaviruses of various origins. Data analysis was performed using the YASS, genomic texts were downloaded from the GISAID, the custom genomic data processing pipeline based on the Galaxy bioinformatics platform was also applied. The article presents the results of an analysis of the available scientific literature and the computational experiment comparing the genomic texts of Belarusian coronavirus samples with a number of selected complete genomes of dangerous and especially dangerous viruses and coronaviruses of various origin. A significant similarity of the new coronavirus with the recombinant coronavirus, as well as partial similarity with synthetic coronavirus, Rubella, Ebola 1976, HIV-2 (human immunodeficiency virus), Middle East respiratory syndrome, simian immunodeficiency and Marburg fever viruses have been found.